Pre-professional ideologies and career trajectories of the allied professional undergraduate student. Issue 2 (3rd April 2017) - Hosein, Anesa; Rao, Namrata
Abstract: Undergraduate students sometimes pursue degrees that are aimed at allied jobs. This research examines how students in one allied professional degree, education studies, conceptualise their pre-professional ideology and how these ideologies relate to their intended career trajectory. The research draws upon a year-long qualitative survey of over 70 undergraduate students. Students' professional ideology and career path were initially linked to the corresponding professional degree – teacher education. Over the year, students' conceptualisation of their pre-professional ideology changed but their career trajectory remained relatively constant. These findings imply students were conforming or socialising into the expectations of their allied professional discipline but did not have an expectation to follow that career path. The research findings have implications for helping students to be realistic about their career trajectory and ensuring that they are prepared for an appropriate job.